Z Boson Production via p-p and Pb-Pb Collisions at spp=5.02 TeV - Leonard S. Kisslinger; Debasish Das (Advances in High Energy Physics)
We estimate the production of Za bosons, with a as the component of a Z vector boson, via p-p collisions using previous work on J/Ψ,Ψ2S production in p-p collisions, with the new aspect being the creation of Za bosons via quark interactions. We then estimate the production of Za bosons via Pb-Pb collisions using modification factors from previous publications.